2002
DOI: 10.1002/er.848
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of investments in the pulp and paper industry On investments in the chemical recovery cycle at a board mill

Abstract: SUMMARYIn the pulp and paper industry, energy costs represents a relatively large proportion of the value of production. When investing in new equipment, considerations concerning boundary conditions, such as electricity and oil prices, are therefore of great importance. A vital requirement is the identification of other key parameters influencing production costs as well as possible interaction between these parameters. In this paper, a sensitivity analysis is accomplished by using an optimization model that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…pulp and paper, forest, automobile manufacturing and chemical) to study both economic and environmental aspects (e.g. CO2 emission impact) [25][26][27][28]. A more through description of the method can be found in [21].…”
Section: Energy Systems Modeling Toolmentioning
confidence: 99%
“…pulp and paper, forest, automobile manufacturing and chemical) to study both economic and environmental aspects (e.g. CO2 emission impact) [25][26][27][28]. A more through description of the method can be found in [21].…”
Section: Energy Systems Modeling Toolmentioning
confidence: 99%
“…The reMIND tool has been used in several industries, such as the Swedish foundry industry [2], steel industry [4,[35][36] and pulp and paper mills [6,39] as well as district heating systems [7]. In these studies the ESO tool reMIND is used to find the optimal operation strategy and investigate how different boundary conditions, such as changes in electricity and fuel prices, influence the system.…”
Section: Energy Systems Optimisation (Eso) Toolmentioning
confidence: 99%
“…However, it has been shown that many of these difficulties may be solved by DES and ESO tools [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The ESO tool has been used in several industries, such as the Swedish foundry industry [2], steel industry [3,4] and pulp and paper mills [5,6], as well as in district heating systems [7] and waste treatment [8].…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that mixed-integer linear programming (MILP) provides a methodology for determining optimal strategies in order to minimise the overall energy costs in such industries [16]. Studies using such a methodology in a Swedish context include for example [17][18][19][20][21][22][23][24], where MIND (Method for analysis of INDustrial energy systems) was used. MIND is a method developed for optimization of dynamic industrial energy systems [17].…”
Section: Introductionmentioning
confidence: 99%
“…These studies comprise large energy-intensive sites such as Swedish pulp and paper mills and steelworks, e.g. [17][18][19][20][21][22][23][24]. The need to apply the method in other sectors, including small and medium-sized manufacturers such as the Swedish foundry industry, cannot be understated.…”
Section: Introductionmentioning
confidence: 99%